Konsep Berkah dalam Epistemologi Islam - Busyroel Basyar, Achmad Beadie (JURNAL PUSAKA : Media Kajian dan Pemikiran Islam, 2022)
One of the basic elements of pesantren is a unique value system. And one of those value systems is the concept of blessing. The meaning of barokah has implications for the pattern of student relations in their lives, including its relation to the knowledge sought. The blessing that is closely related to obedience to the kiai is associated with the learning process, and even becomes an indicator of the success of the learning process itself. The meaning of blessing and its concept needs to be understood in depth, both about the components, elements, terms and prerequisites. So that it will also affect the pattern of relationships, communication, and decision making in everyday life, especially regarding the learning process. This research is a qualitative descriptive study. This type of research is a literature study. Where the data sources are obtained from literature references, books, research reports, and others. Then critically processed to find conclusions from these results.Tabarruk means seeking blessings. Barokah is the nature of increasing goodness in something. In Islamic epistemology, tabarruk is in two discussions. First, tabarruk is part of the irfani method. Second, the aspects that are expected to be blessed in tabarruk are not only knowledge, but can be in various aspects of life. Key words: berkah, Islam, epistemology, education, media.